STUDY ON THE CAGE STRENGTH OF CONSTANT VELOCITY JOINT UNDER LIMIT ANGLE - HOU WenLiang; LU Xi; WANG MengFei (Jixie qiangdu)
Cage is one of the key components of constant velocity joint.The cage is in the dangerous situation when the CV joint in the limit Angle,thus the strength of the cage under the limit Angle plays an important role in meeting the requirements for the design and manufacturing.The strength of cage was studied by experiment and the finite element simulation.First of all,stress state and dangerous area were obtained through simulation under the condition of the limit Angle and torque.The fracture torque of the cage was studied by torsion test.Finally,the hardness of the cage was measured by the micro hardness tester,and the distribution regulation that the strength of the cage was obtained by the transformation of the hardness and strength.The results show that the cage strength meets the requirements.This study can provide technical basis for design and manufacturing.